Digital heritage preservation - Stančić, Hrvoje (Array, 2010)
The author firstly discus what kind of digital objects are becoming recognized as digital heritage. He explains the advantages of 3D digitization over the 2D digitization of 3D objects and argues that there is a growing trend in the creation of such digital objects. Than, the author tries to foresee and explain the problems and risks associated with the long-term preservation of digital heritage which are specific for the digital domain. He categorizes them into ten different subcategories, each one having an important impact on the preservation activities. After that analysis, the author addresses indicated problems and tries to give an advice for each of them. Finally, the author concludes that the long-term preservation of digital heritage is a complex but surmountable problem if approached correctly and in time.